Lucio Phenomenon Mimicking Necrotizing Myofasciitis: A Case Report Study - Nurhidayati, Elita; Dyah Ayu Saraswati, Putu (Riviera Publishing, 2025)
Lucio phenomenon is a rare but severe lepra reaction occurring in untreated patients with diffuse lepromatous leprosy, characterized by widespread cutaneous necrosis due to endothelial invasion and vascular thrombosis caused by Mycobacterium leprae. Its clinical resemblance to necrotizing soft tissue infections often leads to diagnostic confusion and inappropriate surgical intervention. We report a case of a 47-year-old man presenting with bilateral necrotic ulcers of the lower limbs, initially diagnosed as necrotizing myofasciitis and scheduled for debridement. However, further dermatological evaluation revealed hallmark signs of multibacillary leprosy, including madarosis, multiple anesthetic plaques, and sensory loss, in the absence of peripheral nerve thickening. A diagnosis of Lucio phenomenon was established, and surgical intervention was withheld in favor of initiating multidrug therapy (MDT) and supportive care. This case underscores the critical importance of early dermatological consultation and high clinical suspicion for atypical leprosy reactions in endemic regions, particularly in patients with rapidly progressive ulcers mimicking necrotizing infections.